2013
DOI: 10.1007/s11434-013-5953-5
|View full text |Cite
|
Sign up to set email alerts
|

Water solubility in orthopyroxene: Dependence on temperature and Al content

Abstract: The water solubility in Al-Fe-Mg orthopyroxene [(Mg,Fe,Al)(Si,Al)O 3 : X Fe = 0.1] was investigated as a function of temperature and Al contents. Experiments were performed at 10 kbar with temperatures ranging from 800 to 1200°C under water-saturated conditions. Water contents in the (Mg,Fe)SiO 3 -H 2 O-Al 2 O 3 system were determined using unpolarized Fourier transform infrared spectroscopy. The present results show that water solubility in Al-bearing orthopyroxene decreases systematically with temperature fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Experiments have shown that the water incorporation in pyroxene also depends on P-T conditions [Rauch and Keppler, 2002;Mierdel and Keppler, 2004;Mierdel et al, 2007;F erot and Bolfan-Casanova, 2012;Zhang et al, 2013] and water activity [Stalder et al, 2008]. In addition, oxygen fugacity is also believed to control the incorporation of water in mantle peridotite NAMs [Peslier et al, 2002;Peslier, 2010;Yu et al, 2011].…”
Section: 1002/2016gc006767mentioning
confidence: 99%
“…Experiments have shown that the water incorporation in pyroxene also depends on P-T conditions [Rauch and Keppler, 2002;Mierdel and Keppler, 2004;Mierdel et al, 2007;F erot and Bolfan-Casanova, 2012;Zhang et al, 2013] and water activity [Stalder et al, 2008]. In addition, oxygen fugacity is also believed to control the incorporation of water in mantle peridotite NAMs [Peslier et al, 2002;Peslier, 2010;Yu et al, 2011].…”
Section: 1002/2016gc006767mentioning
confidence: 99%
“…2) At room temperature, the tensile strength of AZ91D with Gd is increased by 22% and the elongation can be increased by 32%; at high temperature, the tensile strength and elongation could enhance 17% and 25%, respectively. 3) The optimum performance of Mg alloys was obtained when the content of Gd is 2 wt.%, 4) The fracture type of AZ91D magnesium alloy is brittle fracture.…”
Section: Discussionmentioning
confidence: 94%